2023
DOI: 10.1200/jco.22.01705
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hepatic Perfusion With Melphalan for Patients With Isolated Uveal Melanoma Liver Metastases: A Multicenter, Randomized, Open-Label, Phase III Trial (the SCANDIUM Trial)

Abstract: PURPOSE About half of patients with metastatic uveal melanoma present with isolated liver metastasis, in whom the median survival is 6-12 months. The few systemic treatment options available only moderately prolong survival. Isolated hepatic perfusion (IHP) with melphalan is a regional treatment option, but prospective efficacy and safety data are lacking. METHODS In this multicenter, randomized, open-label, phase III trial, patients with previously untreated isolated liver metastases from uveal melanoma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
(44 reference statements)
0
13
1
Order By: Relevance
“…Other hepatic artery–based methods include isolated hepatic infusion (IHP), which is a more invasive procedure than PHP, and hepatic artery infusion (HAI) therapies. In the randomized SCANDIUM trial, IHP with melphalan led to a significantly improved response rate (RR) and PFS than investigator choice therapy 84 . Although OS was numerically superior for IHP at 2 years, it did not reach statistical significance 84 .…”
Section: Management Of Metastatic Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Other hepatic artery–based methods include isolated hepatic infusion (IHP), which is a more invasive procedure than PHP, and hepatic artery infusion (HAI) therapies. In the randomized SCANDIUM trial, IHP with melphalan led to a significantly improved response rate (RR) and PFS than investigator choice therapy 84 . Although OS was numerically superior for IHP at 2 years, it did not reach statistical significance 84 .…”
Section: Management Of Metastatic Uveal Melanomamentioning
confidence: 99%
“…In the randomized SCANDIUM trial, IHP with melphalan led to a significantly improved response rate (RR) and PFS than investigator choice therapy 84 . Although OS was numerically superior for IHP at 2 years, it did not reach statistical significance 84 . The EORTC 18021 trial compared fotemustine-HAI with intravenous fotemustine and, as with the SCANDIUM trial, demonstrated an improved RR without a survival benefit 85 …”
Section: Management Of Metastatic Uveal Melanomamentioning
confidence: 99%
“…There have been several liver-directed therapies that have been investigated in the metastatic uveal setting, both randomized and nonrandomized. The two randomized studies, FOCUS and SCANDIUM, utilized intrahepatic melphalan as the intervention and both demonstrated statistically significant improvements in PFS and overall response rate (ORR) as compared to best alternative care [122,123]. However, the OS data on these studies are still pending and these invasive procedures are typically only available at specialized tertiary cancer centres.…”
Section: Justificationmentioning
confidence: 99%
“…If diagnosed at this early stage, local lesions can be successfully removed with surgery. However, melanoma can rapidly transition to a vertical growth stage, in which it invades the dermis and then metastasizes to lymph and distant organs such as the lungs [ 7 , 8 ], liver [ 9 ] and brain [ 10 ](stage III and IV, respectively), and these later stages are associated with a sharp decline in median 5-year survival [ 11 ]. Therefore, it is necessary to explore the molecular mechanisms that lead to melanoma development and metastasis, and to discover other therapeutic targets and biomarkers to improve patient survival.…”
Section: Introductionmentioning
confidence: 99%